Psychological well-being, coping strategies and incident reports of children affected by Guimaras oil spill - Primero, Lorilla A.; Salcedo, Cecille Judee V.
This study sought to determine the psychological well-being and coping strategies of children affected by oil spill in Brgy. Tando, Nueva Valencai, Guimaras. Thirty two children affected by oil spill in Brgy. Tando, Nueva Valencia, Guimaras. Results showed that children registered an average level of psychological well-being despite of the incident. They were more relaxed and have a better self esteem after a year of the incident.
Thesis (BA-Psychology-Management)--UP Visayas, Miag-ao, Iloilo
Keywords: Coping behavior; Guimaras Oil Spill